1997
DOI: 10.2118/30577-pa
|View full text |Cite
|
Sign up to set email alerts
|

Well Testing for Radially Heterogeneous Reservoirs Under Single and Multiphase Flow Conditions

Abstract: Summary In this work, we examine the behavior of pressure transient data for single and multiphase flow in heterogeneous reservoirs. In order to illustrate multiphase flow behavior in these systems, we focus on heterogeneous gas condensate reservoirs, however, we also consider other multiphase flow problems. It is well known that in some instances, e. g., water injection/falloff in homogeneous reservoirs, pressure transient data from buildup (or falloff) tests cannot be obtained by superposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 7 publications
1
49
0
Order By: Relevance
“…Among the three mentioned methods, only the Perrine's method has been widely used in industry due to its simplicity. Thompson and Reynolds (1997) defined a theoretical expression for pressure derivative in a radially heterogeneous reservoir under multiphase flow condition. They showed that the pressure derivative which is observed at the well bore reflects a weighted harmonic average permeability over the radial extent of the reservoir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the three mentioned methods, only the Perrine's method has been widely used in industry due to its simplicity. Thompson and Reynolds (1997) defined a theoretical expression for pressure derivative in a radially heterogeneous reservoir under multiphase flow condition. They showed that the pressure derivative which is observed at the well bore reflects a weighted harmonic average permeability over the radial extent of the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we developed a theoretical model based on Thompson and Reynolds (1997) equation which represents the pressure derivative that is observed at the wellbore as well as the effects on semi log analysis. The theoretical model applications are demonstrated using a simulation in the reservoir which is filled by oil and water with the variety of saturations at the initial condition.…”
Section: Introductionmentioning
confidence: 99%
“…As pressure data at producing wells are quite sensitive to changes in total mobility (Thompson and Reynolds, 1997), it is not completely surprising that one can obtain reasonable estimates of water relative permeability model parameters even if we history match only pressure data corresponding to times prior to water breakthrough. It is not clear why the information content of the GOR data is sufficient to resolve the parameters defining the oil and water relative permeability curves for the twophase water-oil system.…”
Section: Example 1amentioning
confidence: 99%
“…Many theoretical analytical techniques are available to gain significant information on the subsurface structure (de Marsily, 1986;Ehlig-Economides et al, 1994;Kuchuk, 1995;Shanyan and Wong, 1998;Thompson and Reynolds, 1997). Similarly, large-scale regional groundwater models have generally performed well (National Resource Council, 1990).…”
Section: Single Phase Isothermal Flow and Transportmentioning
confidence: 99%